Trade, Aid, Remittances and Migration - Sule Akkoyunlu (ETH Zurich, KOF Swiss Economic Institute, 2009)
I investigated whether migration is interrelated with trade, aid and remittances so that any policies that consider trade, aid and remittances also affect the decision to migrate. We developed and estimated an empirical model of Turkish migration to Germany and tested the model for the 1969-2004, using the cointegration technique. A single cointegrating vector is found among the gross migration inflows and the following explanatory variables: the relative income ratio between Germany and Turkey, the unemployment rates in Germany and Turkey, aid, the trade intensity variable and the ratio of manufacturing exports with Germany to total exports with Germany and remittances as a ratio of Turkish GDP. The results of this study show that migration, trade, aid and remittances are interrelated, however, migration will be better managed when the dynamic gains from trade and aid are considered. Hence, the broad-based and rapid economic development with increase in income is the only effective means of reducing migration pressures in a labour-surplus country. This is mainly because the income differential is the most significant factor in determining migration flows.
Keywords: C22; F16; F22; F24; F35; 330; Trade; Aid; Remittances; Migration; Cointegration; Auswanderung; Türkei; Rücküberweisung (Migranten); Entwicklungshilfe; Internationale Wirtschaftsbeziehungen; Kointegration; Schätzung; Deutschland